Highly Selective Fluorogenic Multianalyte Biosensors Constructed via Enzyme-Catalyzed Coupling and Aggregation-Induced Emission - Wang, Xiaorui; Hu, Jinming; Zhang, Guoying; Liu, Shiyong (Journal of the American Chemical Society, 2014)
The development of a highly selective and fast responsive fluorogenic biosensor for diverse analytes ranging from bioactive small molecules to specific antigens is highly desirable but remains a considerable challenge. We herein propose a new approach by integrating substrate-selective enzymatic reactions with fluorogens exhibiting aggregation-induced emission feature. Tyrosine-functionalized tetraphenylethene, TPE-Tyr, molecularly dissolves in aqueous media with negligible fluorescence emission; upon addition of horseradish peroxidase (HRP) and H2O2, effective cross-linking occurs due to HRP-catalyzed oxidative coupling of tyrosine moieties in TPE-Tyr. This leads to fluorescence emission turn-on and fast detection of H2O2 with high sensitivity and selectivity. As a validation of the new strategy’s generality, we further configure it into the biosensor design for glucose through cascade enzymatic reactions and for pathologically relevant antigens (e.g., human carcinoembryonic antigen) by combining with the ELISA kit.